2021
DOI: 10.3390/ijms222413431
|View full text |Cite
|
Sign up to set email alerts
|

Hippo Pathway in Regulating Drug Resistance of Glioblastoma

Abstract: Glioblastoma (GBM) represents the most common and malignant tumor of the Central Nervous System (CNS), affecting both children and adults. GBM is one of the deadliest tumor types and it shows a strong multidrug resistance (MDR) and an immunosuppressive microenvironment which remain a great challenge to therapy. Due to the high recurrence of GBM after treatment, the understanding of the chemoresistance phenomenon and how to stimulate the antitumor immune response in this pathology is crucial. The deregulation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 209 publications
1
8
0
Order By: Relevance
“…Conversely, we found that overexpression of GMPPB in GBM decreases the expression of MST1/2 and inhibits the phosphorylation of MOB1, causing the unphosphorylated YAP to escape from the cytoplasm and enter the nucleus, where it binds its transcriptional coactivator (TEAD). Our results build upon and extend previous findings that the interaction of YAP-TEAD prompts cancer cells to act as cancer stem cells, initiating DNA replication procedures, and triggering tumor proliferation, progression, and metastasis [28,30,40,45]. Despite the contributions provided by our study, the direct link between GMPPB and the Hippo pathway remains elusive, although there are multiple reports providing important clues.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Conversely, we found that overexpression of GMPPB in GBM decreases the expression of MST1/2 and inhibits the phosphorylation of MOB1, causing the unphosphorylated YAP to escape from the cytoplasm and enter the nucleus, where it binds its transcriptional coactivator (TEAD). Our results build upon and extend previous findings that the interaction of YAP-TEAD prompts cancer cells to act as cancer stem cells, initiating DNA replication procedures, and triggering tumor proliferation, progression, and metastasis [28,30,40,45]. Despite the contributions provided by our study, the direct link between GMPPB and the Hippo pathway remains elusive, although there are multiple reports providing important clues.…”
Section: Discussionsupporting
confidence: 82%
“…The Hippo pathway has been mapped out over the last several decades of study [26,27]. Two key proteins involved in transcriptional control of the Hippo pathway, Yes-associated protein (YAP) and transcriptional co-activator with PDZ-binding motif (TAZ), have been implicated in the progression of multiple human cancers [28,29], including GBM tumorigenesis and multi-drug resistance [30,31]. Matrix metalloproteinases (MMPs) are a group of enzymes that are shown to mediate carcinogenesis in both a physiological and pathological manner [32].…”
Section: Introductionmentioning
confidence: 99%
“…Abnormal YAP activation in the Hippo pathway significantly reduced the efficacy of targeted therapy and enhanced resistance to epidermal growth factor receptor (EGFR) tyrosine kinase inhibitors in lung cancer 33 . Furthermore, evidence showed that the Hippo pathway was involved in glioma progression and activation of chemoresistance mechanisms 34 . Dysregulation of the YAP/transcriptional coactivator with PDZ-binding motif (YAP/TAZ) signaling may be an important mechanism of intrinsic and acquired resistance to targeted therapies and chemotherapy 35 .…”
Section: Discussionmentioning
confidence: 99%
“…The transcription factor IRF3 is essential for innate antiviral immunity. IRF3 is a critical yes-associated protein (YAP) activator, probably involved in GBM chemoresistance via the Hippo pathway [46,47]. CD274, the gene encoding PD-L1, is commonly used in immunotherapy and presents effectiveness against many cancer types [48,49].…”
Section: Discussionmentioning
confidence: 99%